Mitigation of Barriers throughout the Talent Acquisition Process in an Emerging Market : BOSCH Limited in India - Carle, Max Ralph; Linhartová, Lucie; Říhová, Gabriela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This Master’s Thesis explores the challenges and barriers of talent acquisition in an emerging market, namely, India. BOSCH Limited in India served as a qualitative research example. The most effective solutions and mitigation methods are also discussed. Throughout the thesis, in-depth interviews with BOSCH talent acquisition leaders, long-term employees and new recruits were consolidated into a section on practical data collection. All interviewees highlighted specific details about the talent acquisition process and they personally selected BOSCH as their employer of choice. The results of the literature review are analyzed and compared to the in-depth interviews. The author attempted to present the reader with a practical thesis with interesting insights about talent acquisition within the emerging market of India. The most frequently occurring challenges are: competition of talent, skill gaps, wrong hires, and candidate experience at BOSCH Limited in India. The author proposes a practical solution to all these challenges: implementing a new hiring strategy with a new talent pipeline scheme. This provides benefits to both parties: the company and the workforce. The suggested strategy provides a cost-effective way to mitigate the challenges and barriers whilst also giving individuals and talent the chance to gain more professional experience and leaving them with a longer period of skill acquisition. It allows BOSCH Limited to secure talent internally, but also to hire external talent with incentives provided by TA professionals.
Vedoucí práce: Lucie Linhartová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses